2013
DOI: 10.1105/tpc.113.112391
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Genetic Basis for Leaf Morphology in a Set of Precisely Defined Tomato Introgression Lines

Abstract: Introgression lines (ILs), in which genetic material from wild tomato species is introgressed into a domesticated background, have been used extensively in tomato (Solanum lycopersicum) improvement. Here, we genotype an IL population derived from the wild desert tomato Solanum pennellii at ultrahigh density, providing the exact gene content harbored by each line. To take advantage of this information, we determine IL phenotypes for a suite of vegetative traits, ranging from leaf complexity, shape, and size to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
259
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(283 citation statements)
references
References 90 publications
(128 reference statements)
16
259
2
2
Order By: Relevance
“…esculentum (Slyc). Previous studies using this IL population have identified numerous QTL (Lippman et al 2007) for traits ranging from fruit metabolite concentrations (Schauer et al 2006), yield , reproductive isolation , and leaf traits (Holtan and Hake 2003;Chitwood et al 2013). With these data, we confirm evidence in support of adaptive evolution of leaf traits, examine the physiological and ecological significance of trait variation in several clearly adaptive traits, and identify potential molecular developmental mechanisms responsible for this trait variation.…”
supporting
confidence: 73%
“…esculentum (Slyc). Previous studies using this IL population have identified numerous QTL (Lippman et al 2007) for traits ranging from fruit metabolite concentrations (Schauer et al 2006), yield , reproductive isolation , and leaf traits (Holtan and Hake 2003;Chitwood et al 2013). With these data, we confirm evidence in support of adaptive evolution of leaf traits, examine the physiological and ecological significance of trait variation in several clearly adaptive traits, and identify potential molecular developmental mechanisms responsible for this trait variation.…”
supporting
confidence: 73%
“…The introgressed segments appear as solid bars in which the boundary edge of each segment is indicated by inclusive (+) and exclusive (2) flanking markers. Numbers at the bottom denote the genomic positions according to a previous publication (Chitwood et al, 2013). D, ProSlIPMS3:GFP-GUS plants show GFP expression in the apical cells of type I/IV trichomes.…”
Section: Identification Of a Novel Trichome-expressed Ipms Genementioning
confidence: 99%
“…Discretisation of shape based on evenly spaced marks along the contour and averaging these marks over many leaves allows the proper description and quantification of simple entire leaves (Langlade et al, 2005;Bensmihen et al, 2008;Weight et al, 2008;Feng et al, 2009). Likewise, landmark-independent Fourierbased analysis of the contour is useful to quantify the general shape of the leaf (Chitwood et al, 2012(Chitwood et al, , 2013(Chitwood et al, , 2014. However, because these approaches result in smooth, averaged contours, neither of them is appropriate to accurately capture characteristic structures with a variable position such as teeth or lobes (Chitwood et al, 2012(Chitwood et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%